Assessing the Effectiveness of Vaccination Programs in Reducing Childhood Diseases - Masturapratiwi, Hazhiyah Azima; Nurhalizah, Siti; Utami, Hilda (Journal of Asian-african Focus in Health, 2024)
This study analyzed data gathered from healthcare professionals, parents, and existing health records through questionnaires to objectively evaluate the impact of immunization programs in lowering childhood illnesses. Measles (95.0%), polio (93.5%), diphtheria (91.0%), pertussis (89.5%), and hepatitis B (90.0%) vaccination rates were all high. These illnesses were also found to have low incidence rates, with measles and polio having the lowest rates (0.5 and 0.1 per 1,000, respectively). The effectiveness of vaccination has been found to be influenced by a number of factors, including healthcare accessibility, socioeconomic position, vaccine awareness, perceived vaccine safety, and community engagement. Despite the study's general success, there is always room for improvement, especially in terms of addressing socioeconomic hurdles and preserving pertussis coverage. These results are consistent with previous research and emphasize the necessity for ongoing immunization campaigns, booster shots, and focused community involvement initiatives to improve the efficacy of immunization programs and safeguard children's health throughout the world.